MiR‐30b‐5p attenuates the inflammatory response and facilitates the functional recovery of spinal cord injury by targeting the NEFL/mTOR pathway. Issue 12 (25th October 2022) - Zhang, Hui; Wang, Duojun; Tong, Jinyu; Fang, Jianguo; Lin, Zaijun
Abstract: Background: Neurofilament light chain (NEFL) has been identified as a biomarker for spinal cord injury (SCI), but its effect and underlying mechanism in SCI remain unclear. Methods: SCI rat models were established for in vivo studies. Lipopolysaccharide (LPS)‐induced cell models were used for in vitro studies. The protein and mRNA expression levels of genes were evaluated by western blotting and reverse transcription‐quantitative polymerase chain reaction (RT‒qPCR). The pathological changes in rats after SCI were subjected to histological examinations. The interaction of NEFL and upstream miRNAs was explored using dual‐luciferase reporter gene assays. Results: NEFL was highly expressed in SCI rat spinal cord tissues and LPS‐stimulated PC12 cells. NEFL silencing showed an inhibitory effect on the morphological changes of SCI rats and the secretion of inflammatory factors and facilitated functional recovery of SCI rats. MiR‐30b‐5p was demonstrated to target NEFL and negatively regulate NEFL mRNA and protein levels. Downregulation of miR‐30b‐5p in SCI cell and rat models was demonstrated. MiR‐30b‐5p alleviated the inflammatory response in SCI rat models and LPS‐stimulated PC12 cells and promoted functional recovery in rats by targeting NEFL. NEFL activated mTOR signaling. MiR‐30b‐5p inactivated mTOR signaling by negatively regulating NEFL. Conclusion: MiR‐30b‐5p alleviated the inflammatory response and facilitated the functional recovery of SCI rats by targeting NEFL to inactivate the mTOR pathway. Abstract : Silencing of NEFL inhibits the inflammatory response and functional recovery following spinal cord injury.